Blue dye degradation effect of green chemical synthesized CuO nanoparticles. (2022) - Arunkumar, B.; Jothibas, M.; Johnson Jeyakumar, S.
Abstract: This extant work, sol–gel experiment effect of green synthesized CuO nanoparticles using Lantana Camara (LC) and Wrightia Tinctoria (WT) leaf extracts for optical and Photocatalytic analysis. LC and WT leaf extracts via Sol-gel method exhibit the enhanced optical and Photocatalytic activities. Characterization of XRD analysis shows that leaf extract capped CuO nanoparticles coordinated with CuO structure and Phase lattice. The particles are very much scattered circular, going with practically all around characterized and uniform crystalline structure observed in SEM image. The Photoluminescence analysis exhibit the amplified green emissions, caused by the plant extract (LC & WT) ions incorporated with Cu ions to developed the CuO nanoparticle for optical properties. The sun light irradiation using plant extract capped CuO Nanoparticles exhibited enriched degradation process for potential application in photocatalytic properties.